Backing material

By using a combined structure of resin and crystal carbon in the backplane material, the problem of difficulty in taking into account both ultrasonic absorption and thermal conductivity in the prior art is solved, and the performance improvement of efficient ultrasonic diagnostic equipment is achieved.

JP2025054387APending Publication Date: 2025-04-08MITSUBISHI PENCIL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023163440
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-26
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing backplane materials are difficult to balance between improving ultrasonic absorption and thermal conductivity, resulting in limited performance of ultrasonic diagnostic equipment.

Method used

A plate-shaped back plate material consisting of a resin portion and a plurality of crystal carbon portions is used, wherein the crystal carbon portions are arranged in a pattern structure, arranged along the thickness direction of the back plate material, and interlaced between the resin portions, and the resin portion occupies 30% to 80% of the volume.

Benefits of technology

It achieves both efficient ultrasonic absorption and high thermal conductivity, and improves the performance of ultrasonic diagnostic equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025054387000001_ABST
    Figure 2025054387000001_ABST
Patent Text Reader

Abstract

To provide a novel backing material having an attenuation factor and a thermal conductivity of an ultrasonic wave.SOLUTION: A backing material 10 of the present invention is a plate-like backing material 10 as shown in Figures 1(a) and 1(b), and includes a resin part 12 and a plurality of crystalline carbon parts 14. The crystalline carbon parts 14 are arranged in a direction directed to a second surface B that faces a first surface A from the first surface A of the backing material 10, and a percentage content of the resin part 12 is 30 mass% or more and 80 mass% or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a backing material. [Background technology]

[0002] Medical ultrasound diagnostic devices and ultrasound imaging devices transmit ultrasound signals to an object and receive reflected signals (echo signals) from within the object to create an image of the object. These ultrasound diagnostic devices and ultrasound imaging devices mainly use array-type ultrasound probes that have the ability to transmit and receive ultrasound signals.

[0003] An ultrasonic probe includes, from the target side, an acoustic lens, an acoustic matching layer, a piezoelectric element, and a backing material in this order. The backing material constituting such an ultrasonic probe is required to have performance such as good ultrasonic attenuation to improve sensitivity and high thermal conductivity to prevent overheating of the piezoelectric element. Various types of such backing materials have been proposed.

[0004] Patent Document 1 discloses a backing material for an ultrasonic probe, which is substantially made of porous amorphous carbon.

[0005] Patent Document 2 discloses an ultrasonic probe having a piezoelectric element and a backing material containing a matrix resin and thermally conductive particles arranged on one side of the piezoelectric element, the ratio of thermal conductivity in the thickness direction to the horizontal direction of the backing material being equal to or greater than 3. Patent Document 2 discloses various simple metals and metal compound particles as the thermally conductive particles. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2019-193151 A [Patent Document 2] Patent Publication No. 2021-062170 Summary of the Invention [Problem to be solved by the invention]

[0007] The backing material of Patent Document 1 provides good ultrasonic attenuation, good processability, and good resistance to deterioration over time, but there is room for improvement in terms of thermal conductivity.

[0008] In addition, although good thermal conductivity is obtained in Patent Document 2, there is room for improvement in terms of the attenuation rate of ultrasonic waves.

[0009] Therefore, the present invention provides a novel backing material that combines ultrasonic attenuation rate and thermal conductivity. [Means for solving the problem]

[0010] As a result of intensive research, the present inventors have found that the above problems can be solved by the following means, and have completed the present invention. That is, the present invention is as follows: <Aspect 1> A plate-shaped backing material, The resin portion and the crystalline carbon portion are included. The crystalline carbon portions are arranged in a direction from a first surface of the backing material to a second surface opposite to the first surface, and The content of the resin part is 30% by volume or more and 80% by volume or less. Backing material. <Aspect 2> The backing material according to aspect 1, wherein the graphene structure of the crystalline carbon constituting the crystalline carbon portion is oriented in the thickness direction of the backing material. <Aspect 3> Each of the plurality of crystalline carbon portions has a planar region, and the planar regions are arranged approximately parallel to one another in a direction from a first surface of the backing material toward a second surface opposite to the first surface, and The resin portion is interposed between two adjacent crystalline carbon portions. 3. The backing material according to claim 1 or 2. <Aspect 4> Each of the plurality of crystalline carbon portions has a rod-shaped region, and the rod-shaped regions are arranged approximately parallel to each other in a direction from a first surface of the backing material toward a second surface opposite to the first surface, and The resin portion is interposed between two adjacent crystalline carbon portions. 3. The backing material according to claim 1 or 2. Aspect 5: The backing material according to any one of aspects 1 to 4, having a thermal conductivity in accordance with JIS R1611-2010 of 35.0 W / m·K or more. Aspect 6: The backing material according to any one of aspects 1 to 5, having an acoustic impedance of 2.0 to 6.0 Mrayl. <Aspect 7> The backing material according to any one of aspects 1 to 6, wherein the crystalline carbon portion has a peak ratio (G / D) in a Raman spectrum of 2.0 or more. Aspect 8: The backing material according to any one of aspects 1 to 7, having an ultrasonic attenuation rate of 1.5 dB / mm or more at a frequency of 1 MHz. Aspect 9: An ultrasonic probe having, in this order, an acoustic lens, an acoustic matching layer, a piezoelectric element, and the backing material according to any one of aspects 1 to 8. Effect of the Invention

[0011] According to the present invention, it is possible to provide a novel backing material that combines a good ultrasonic attenuation rate and good thermal conductivity. [Brief description of the drawings]

[0012] [Figure 1] Fig. 1(a) is a top view of a backing material according to a first embodiment of the present invention, and Fig. 1(b) is a side cross-sectional view taken along line Ib-Ib in Fig. 1(a). [Diagram 2] Fig. 2(a) is a top view of a backing material according to a second embodiment of the present invention, and Fig. 2(b) is a side cross-sectional view taken along line IIb-IIb in Fig. 2(a). [Diagram 3]Fig. 3(a) is a top view of the backing material of the present invention. Fig. 3(b) is a side cross-sectional view taken along line IIIb-IIIb in Fig. 3(a). Fig. 3(c) is a side cross-sectional view taken along line IIIc-IIIc in Fig. 3(a). Fig. 3(d) is a side cross-sectional view taken along line IIId-IIId in Fig. 3(a). Fig. 3(e) is a side cross-sectional view taken along line IIIe-IIIe in Fig. 3(a). Fig. 3(f) is a top cross-sectional view taken along line IIIf-IIIf in Fig. 3(d). [Figure 4] FIG. 4 is an explanatory diagram of the measurement of ultrasonic attenuation rate. [Diagram 5] FIG. 5 is a side cross-sectional view of the ultrasonic probe of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] <Backing material> As shown in FIGS. 1(a) and 1(b), the backing material 10 of the present invention is a plate-shaped backing material 10, The resin portion 12 and a plurality of crystalline carbon portions 14 are included. The crystalline carbon portions 14 are arranged in a direction from a first surface A of the backing material 10 toward a second surface B opposite to the first surface A, and The content of the resin portion 12 is 30% by volume or more and 80% by volume or less.

[0014] The inventors have found that the above-mentioned configuration makes it possible to obtain a backing material that has both ultrasonic attenuation and thermal conductivity. Without wishing to be bound by theory, this is believed to be due to the fact that the crystalline carbon portion with good thermal conductivity is arranged in a direction from the first surface to the second surface of the backing material while taking advantage of the good ultrasonic attenuation rate of the resin, thereby allowing efficient heat transfer.

[0015] As shown in Figures 1(a) and (b), the backing material 10 of the present invention may have a plurality of crystalline carbon portions 14 each having a planar region, the planar regions being arranged approximately parallel to one another in a direction from a first surface A of the backing material toward a second surface B opposite the first surface A, and a resin portion 12 being interposed between adjacent crystalline carbon portions 14.

[0016] In the present invention, "approximately parallel" means that the difference from a completely parallel angle is within 10°, within 5°, within 3°, or within 1°.

[0017] Furthermore, as shown in Figures 2(a) and (b), the backing material 10 of the present invention may have a plurality of crystalline carbon portions 14 each having a rod-shaped region, the rod-shaped regions being arranged approximately parallel to one another in a direction from a first surface A of the backing material toward a second surface B opposite the first surface A, and a resin portion 12 being interposed between two adjacent crystalline carbon portions 14.

[0018] In this embodiment, as shown in Figures 3(a) to (f), the film may further include another crystalline carbon portion 14b arranged substantially parallel to the surface direction. As shown in Figures 3(a) to (f), the other crystalline carbon portion 14b may be rod-shaped.

[0019] The thermal conductivity of the backing material of the present invention in accordance with JIS R1611-2010 can be 35.0 W / m·K or more, 40.0 W / m·K or more, 45.0 W / m·K or more, 50.0 W / m·K or more, 55.0 W / m·K or more, 60.0 W / m·K or more, 65.0 W / m·K or more, 70.0 W / m·K or more, 75.0 W / m·K or more, 80.0 W / m·K or more, 85.0 W / m·K or more, or 90.0 W / m·K or more.

[0020] The acoustic impedance of the backing material of the present invention can be 2.0 Mrayl or greater, 2.5 Mrayl or greater, 3.0 Mrayl or greater, 3.5 Mrayl or greater, 4.0 Mrayl or greater, 4.5 Mrayl or greater, or 5.0 Mrayl or greater.

[0021] The above acoustic impedance is calculated by the following formula. Acoustic impedance (Z: Mrayl) = density (ρ: g / cm 3 )×Sound velocity (C:m / sec) / 10 3

[0022] Here, the above sound velocity may be the sound velocity measured in accordance with, for example, JIS Z 2353-2003.

[0023] The density of the backing material having the above structure is 1.55 g / cm 3 The density can be 1.50 g / cm or less. 3 Below 1.45g / cm 3 or less than 1.40 g / cm 3 It can be less than or equal to 0.90 g / cm 3 More than 0.95g / cm 3 More than 1.00g / cm 3 More than 1.10g / cm 3 More than 1.20g / cm 3 or more, or 1.25g / cm 3 It can be more than that.

[0024] The ultrasonic attenuation rate of the backing material of the present invention at a frequency of 1 MHz can be 1.5 dB / mm or more, 2.0 dB / mm or more, 2.5 dB / mm or more, 3.0 dB / mm or more, 3.5 dB / mm or more, 4.0 dB / mm or more, 4.5 dB / mm or more, 5.0 dB / mm or more, or 5.5 dB / mm or more.

[0025] 4, this ultrasonic attenuation rate can be obtained by filling a water tank 20 with water at 25°C, arranging a transmitting probe 40, a backing material 10, and a receiving probe 30 in this order, transmitting ultrasonic waves with a frequency of 1 MHz toward the backing material from the transmitting probe 40, receiving the ultrasonic waves that have passed through the backing material by the receiving probe 30, and measuring the amplitude of the ultrasonic waves when they pass through the water (before passing through the backing material) and the amplitude of the ultrasonic waves after passing through the backing material. The attenuation rate can be calculated by the following formula using the ratio A / B of the amplitude A when passing through the water (before passing through the backing material) to the amplitude B after passing through the backing material, and the thickness T of the backing material. Attenuation rate (dB / mm) = {20log 10 (A / B)} / T

[0026] Each component of the present invention will now be described.

[0027] <Resin part> The resin that constitutes the resin portion can be a resin that can effectively attenuate sound waves, such as thermosetting resins such as epoxy resin, furan resin, urethane resin, and phenolic resin, and thermoplastic resins such as rubber and elastomer.

[0028] The presence of the resin as a matrix can impart the damping properties inherent to the resin to the backing material.

[0029] The volume ratio of the resin portion is 30 to 80% by volume relative to the volume of the backing material. From the viewpoint of suppressing attenuation of ultrasonic waves, this volume ratio is preferably 30% by volume or more, 35% by volume or more, 40% by volume or more, 45% by volume or more, 50% by volume or more, 55% by volume or more, or 60% by volume or more. From the viewpoint of thermal conductivity, this volume ratio is preferably 80% by volume or less, 75% by volume or less, or 70% by volume or less.

[0030] <Crystalline carbon part> The crystalline carbon portion is a member substantially made of anisotropic crystalline carbon. Here, in this specification, "substantially made" means that, for example, crystalline carbon occupies 50 to 100 volume % of the crystalline carbon portion. This volume ratio may be 50 volume % or more, 60 volume % or more, 70 volume % or more, 80 volume % or more, or 90 volume % or more, and 100 volume % or less, 98 volume % or less, or 95 volume % or less. The remainder of the crystalline carbon portion may be a resin, particularly a resin that functions as a binder, or a filler other than anisotropic crystalline carbon.

[0031] The crystalline carbon portion may be, for example, an expanded graphite sheet, or may be a member containing crystalline carbon and amorphous carbon.

[0032] The crystalline carbon portion may further contain amorphous carbon, which can be obtained, for example, by carbonizing a carbon precursor in a non-oxidizing atmosphere.

[0033] When the crystalline carbon portion contains amorphous carbon, it is preferable that the content of amorphous carbon is small from the viewpoint of suppressing the loss of thermal conductivity caused by amorphous carbon. Specifically, it is preferable that the peak ratio (G / D) of the Raman spectrum of the crystalline carbon portion is 2.0 or more, 3.0 or more, 5.0 or more, 8.0 or more, 10.0 or more, 11.0 or more, 13.0 or more, 15.0 or more, 17.0 or more, 20.0 or more, or 21.0 or more from the viewpoint of improving the thermal conductivity. This peak ratio may be 100.0 or less, 90.0 or less, 70.0 or less, 50.0 or less, 40.0 or less, 30.0 or less, or 25.0 or less. For example, this peak ratio may be 2.0 to 100.0.

[0034] The peak ratio (G / D) refers to the ratio of the peak intensity of the G band (Graphite band) to the peak intensity of the D band (Disorder band) in the Raman spectrum. The G band is located at 1580 cm -1 Near, for example, 1450-1700 cm-1 This refers to the maximum peak at 1350 cm in the Raman spectrum, which is a peak derived from crystalline carbon. -1 Near, for example, 1100-1450 cm -1 This means the maximum peak of the amorphous carbon, which is a peak derived from amorphous carbon. In other words, a high peak ratio means that the ratio of crystalline carbon is high, that is, the amount of amorphous carbon is low.

[0035] The Raman spectrum was measured under the following conditions. Laser wavelength: 532nm Laser power: 2.0mW Exposure time: 0.1 seconds Number of scans: 10 Magnification of objective lens: 50x, Aperture: 50μm confocal pinhole Grating: 900 lines / mm Measurement wavelength: 50~3400cm -1

[0036] The anisotropic crystalline carbon may be crystalline carbon having anisotropy due to the graphene structure of carbon. As such crystalline carbon, graphite, carbon fiber, etc. can be used.

[0037] As the graphite, for example, graphite particles having a scale-like, spherical, lump-like, thin flake-like shape, etc. can be used.

[0038] As the carbon fiber, for example, milled fiber, chopped fiber, etc. can be used. These may be used alone or in combination.

[0039] From the viewpoint of improving thermal conductivity, it is preferable that the graphene structure of the anisotropic crystalline carbon is oriented in the thickness direction of the backing material. "The graphene structure is oriented in the thickness direction" means that the graphene structure of the crystalline carbon spreads in the thickness direction, and "the graphene structure is oriented in the plane direction" means that the graphene structure of the crystalline carbon spreads in the plane direction.

[0040] 《Ultrasonic probe》 As shown in FIG. 5, the ultrasonic probe 100 of the present invention comprises an acoustic lens 120, an acoustic matching layer 130, a piezoelectric element 140, and the above-mentioned backing material 10 in this order.

[0041] The ultrasonic waves emitted by the piezoelectric element 140 pass through the acoustic matching layer 130 and the acoustic lens 120 in this order, and are transmitted to the target. That is, the backing material 10 is provided on the piezoelectric element 140 that transmits ultrasonic waves to the target, on the side opposite to the transmission direction of the ultrasonic waves from the piezoelectric element 140 to the target.

[0042] Acoustic Lens Acoustic lenses are typically positioned to use refraction to focus an ultrasonic beam and improve resolution.

[0043] In the present invention, examples of materials that can be used to form the acoustic lens include homopolymers such as conventionally known silicone rubber, fluorosilicone rubber, polyurethane rubber, and epichlorohydrin rubber, and copolymer rubbers such as ethylene-propylene copolymer rubber obtained by copolymerizing ethylene and propylene.

[0044] <Piezoelectric element> A piezoelectric element generally has electrodes and a piezoelectric material, and is capable of converting an electrical signal into a mechanical vibration and vice versa, and is capable of transmitting and receiving ultrasonic waves.

[0045] (Piezoelectric materials) The piezoelectric material may be a material capable of converting an electrical signal into a mechanical vibration and vice versa. Examples of the piezoelectric material include piezoelectric ceramics such as lead zirconate titanate (PZT) ceramics and PbTiO3 ceramics, organic polymeric piezoelectric materials such as vinylidene fluoride (VDF) polymers and vinylidene cyanide (VDCN) polymers, quartz, Rochelle salt, and the like.

[0046] Examples of vinylidene fluoride (VDF)-based polymers include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-trifluoroethylene (P(VDF-TrFE)), etc. Examples of vinylidene cyanide (VDCN)-based polymers include polyvinylidene cyanide (PVDCN) and vinylidene cyanide-based copolymers.

[0047] (electrode) For the electrodes, for example, gold (Au), platinum (Pt), silver (Ag), palladium (Pd), copper (Cu), aluminum (Al), nickel (Ni), tin (Sn), etc. can be used.

[0048] <Acoustic matching layer> The acoustic matching layer generally matches the acoustic impedance between the ultrasonic transducer and the subject, and is made of a material having an intermediate acoustic impedance between the ultrasonic transducer and the subject.

[0049] Materials that can be used for the acoustic matching layer include aluminum, aluminum alloys (e.g., AL-Mg alloys), magnesium alloys, Macor glass, glass, fused quartz, copper graphite, polyethylene (PE), polypropylene (PP), polycarbonate (PC), ABC resin, polyphenylene ether (PPE), ABS resin, AAS resin, AES resin, nylon (PA6, PA6-6), PPO (polyphenylene oxide), PPS (polyphenylene sulfide: can also contain glass fiber), PPE (polyphenylene ether), PEEK (polyether ether ketone), PAI (polyamide imide), PETP (polyethylene terephthalate), PC (polycarbonate), epoxy resin, urethane resin, etc.

[0050] The acoustic matching layer may be a single layer or multiple layers.

[0051] <<Manufacturing method of backing material>> The method of the present invention for producing a backing material comprises the steps of: Obtaining a crystalline carbon portion; A resin portion is disposed between the crystalline carbon portions to obtain a molded body for a backing material; and The molded body for the backing material is cut so that the crystalline carbon portion is arranged in a direction from a first surface of the resulting backing material toward a second surface opposite to the first surface, thereby obtaining a backing material. Includes.

[0052] <Provision of crystalline carbon part> The crystalline carbon portion may be provided by placing crystalline carbon in a mold and press-molding it, or may be provided by obtaining a commercially available expanded graphite sheet or the like.

[0053] Alternatively, the crystalline carbon may be dispersed in a carbon precursor such as a resin, and the carbonized in a non-oxidizing atmosphere. The carbonization temperature may be, for example, 800°C or more, 900°C or more, or 1000°C or more, and may be 2000°C or less, 1900°C or less, 1800°C or less, 1700°C or less, 1600°C or less, 1500°C or less, 1400°C or less, 1300°C or less, or 1200°C or less. For example, the carbonization temperature may be 800°C to 2000°C. In this case, it is preferable to perform the carbonization while pressing, from the viewpoint of connecting the crystalline carbon well and thereby improving the thermal conductivity.

[0054] <Preparation of Molded Body for Backing Material> When the crystalline carbon portion is in the form of a plate, the molded body for the backing material can be produced, for example, by alternately arranging the crystalline carbon portion and the resin portion.

[0055] Furthermore, when the crystalline carbon portion is rod-shaped, the molded body for the backing material may be produced by arranging rod-shaped crystalline carbon portions in a lattice pattern, pouring a resin into the lattice, and curing the resin.

[0056] <Cutting of the molded body for backing material> The cutting of the molded body for the backing material is carried out so that at least a part of the crystalline carbon portion is arranged in a direction from a first surface of the resulting backing material toward a second surface opposite to the first surface. EXAMPLES

[0057] The present invention will be specifically described with reference to examples and comparative examples, but the present invention is not limited to these.

[0058] <<Preparation of backing material>> Example 1 Expanded graphite with an average particle size of 180 μm was placed in a mold and press molded to produce a graphite sheet with a size of 20 mm square and a thickness of 0.2 mm. Holes of Φ300 μm were drilled at 1.5 mm intervals in the obtained graphite sheet using a laser processing machine. Here, the graphene structure of the graphite that constitutes the graphite sheet was spread in the plane direction of the graphite sheet.

[0059] 50 graphite sheets were laminated by applying epoxy resin to the obtained graphite sheet and placing another graphite sheet on top of it, and the epoxy resin was cured at 60°C to obtain a molded body of 20 x 20 x 20 mm. The volume ratio of the epoxy resin in this molded body was about 50% by volume.

[0060] The obtained molded body was cut to a thickness of 2 mm so that the graphite sheet was arranged in a direction from one side to the other side of the backing material and the graphite was oriented in the thickness direction, thereby obtaining a backing material of the example. Therefore, in this case, the graphene structure of the graphite constituting the graphite sheet was oriented in the thickness direction of the backing material.

[0061] Comparative Example 1 The molded body obtained in Example 1 was cut to a thickness of 2 mm so that the graphite sheet was arranged in the plane direction of the backing material, to obtain a backing material of Comparative Example 1. Therefore, in this case, the graphene structure of the graphite constituting the graphite sheet was oriented in the plane direction of the backing material.

[0062] Example 2 Diallyl phthalate monomer was added as a plasticizer to 60 parts by mass of polyvinyl chloride resin, 30 parts by mass of flake graphite, and 10 parts by mass of graphite milled fiber (carbon fiber), and the mixture was mixed in a mixer and then kneaded with a three-roll mill.

[0063] The kneaded mixture was pelletized with a pelletizer, and molded into flat rod-like bodies with a cross section of 2 mm × 0.5 mm using a rectangular die in an extrusion molding machine, and then cut into lengths of 40 mm. Here, the graphene structure of the graphite constituting the flat rod-like bodies was parallel to the length direction of the flat rod-like bodies and extended so as to be parallel to the flat surfaces of the flat rod-like bodies.

[0064] The obtained rod-shaped bodies were arranged at 4 mm intervals, and rod-shaped bodies were arranged at 4 mm intervals on top of them so as to be perpendicular to each other. This was repeated to create a lattice-shaped resin molded body of 40 mm length x 40 mm width x 30 mm thickness. This lattice-shaped resin molded body was heated in an air oven at 180 ° C. with a graphite plate placed on it as a weight to form a lattice-shaped carbon precursor, which was then baked and carbonized at 1000 ° C. in nitrogen, and further baked up to 3000 ° C. in argon to obtain a lattice-shaped carbon molded body of 35 mm length x 35 mm width x 15 mm thickness.

[0065] The obtained molded body was impregnated with acrylic resin under reduced pressure and cured to obtain a composite molded body. The volume ratio of the epoxy resin in this composite molded body was about 50 to 60 volume %. After that, the composite molded body was tilted by 90 degrees, and cut to a thickness of 2 mm so that the 35 mm part was in the thickness direction, to obtain the backing material of Example 2.

[0066] In the backing material of Example 2, about half of the flat rod-shaped bodies were arranged in a direction from one surface to the other surface of the backing material. Therefore, the graphene structure of the graphite constituting the flat rod-shaped bodies arranged in a direction from one surface to the other surface of the backing material was oriented in the thickness direction of the backing material.

[0067] Comparative Example 2 80 parts by mass of furan resin and 20 parts by mass of flake graphite (average particle size 5 μm) were added with 3 parts by mass of p-toluenesulfonic acid and 3 parts by mass of methanol liquid as a curing agent, and the mixture was thoroughly stirred at room temperature using a high-speed homomixer while being decompressed and degassed. The solution was poured into a mold with a thickness of 3 mm, heated and cured, and treated in an air oven at 180 ° C for 3 hours to obtain a carbon precursor. The temperature was then raised at 15 ° C per hour in nitrogen gas, and the mixture was held at 1000 ° C for 3 hours to obtain a sheet material with a thickness of 2.3 mm. The sheet material was processed to a thickness of 2 mm to obtain a backing material of Comparative Example 2.

[0068] In the backing material of Comparative Example 2, flake graphite was dispersed and arranged in random directions in the amorphous carbon, and thus the graphene structures of the graphite were arranged in random directions in the backing material.

[0069] The Raman spectrum of the crystalline carbon portion of the obtained backing material was measured under the following conditions. Laser wavelength: 532nm Laser power: 20mW Exposure time: 0.1 seconds Number of scans: 10 Magnification of objective lens: 50x, Aperture: 50μm confocal pinhole Grating: 900 lines / mm Measurement wavelength: 50~3400cm -1

[0070] Measurements were performed at five unique points for each backing material, and the G / D ratio was calculated for each measurement. The arithmetic mean of the G / D ratios at five points for the same backing material was taken as the G / D ratio of the crystalline carbon part of that backing material.

[0071] "evaluation" <Thermal Conductivity> The thermal conductivity of the prepared backing material in the thickness direction was measured using a laser flash thermal property measuring device (LFA457, NETZSCH).

[0072] <Ultrasonic attenuation rate> As shown in Figure 4, a water tank 20 was filled with water at 25°C, and a transmitting probe 40, a backing material 10, and a receiving probe 30 were arranged in that order. Ultrasonic waves with a frequency of 1 MHz were transmitted from the transmitting probe 40 toward the backing material. The ultrasonic waves that passed through the backing material were received by the receiving probe 30, and the amplitude of the ultrasonic waves before and after they passed through the backing material was measured to evaluate the ultrasonic attenuation rate in the thickness direction of each backing material.

[0073] Acoustic impedance In accordance with JIS Z 2353-2003, the sound velocity in the thickness direction of each of the prepared backing materials was measured at 25° C. using a singular sound velocity measuring device. The acoustic impedance was calculated using the calculated density and the measured sound velocity.

[0074] Table 1 shows the configurations and evaluation results of the examples and comparative examples.

[0075] [Table 1]

[0076] From Table 1, it can be seen that the backing materials of the examples in which the crystalline carbon portions are arranged in a direction from the first surface of the backing material to the second surface opposite the first surface, and in which the resin portion content is 45 volume % or more and 80 volume % or less, have good thermal conductivity and attenuation rate. [Explanation of symbols]

[0077] 10 Backing material 12 Resin part 14, 14a, 14b Crystalline carbon part A First Side B. Second Side 20 Aquarium 22 water 30 Receiving transducer 40 Transmitting transducer 100 Ultrasonic transducer 120 Acoustic Lens 130 Acoustic matching layer 140 Piezoelectric element

Claims

1. A plate-shaped backing material, The resin portion and the crystalline carbon portion are included. The crystalline carbon portions are arranged in a direction from a first surface of the backing material to a second surface opposite to the first surface, and The content of the resin portion is 30% by volume or more and 80% by volume or less. Backing material.

2. The backing material according to claim 1 , wherein the graphene structure of the crystalline carbon constituting the crystalline carbon portion is oriented in a thickness direction of the backing material.

3. Each of the plurality of crystalline carbon portions has a planar region, and the planar regions are arranged approximately parallel to one another in a direction from a first surface of the backing material toward a second surface opposite to the first surface, and The resin portion is interposed between two adjacent crystalline carbon portions. The backing material according to claim 1 or 2.

4. Each of the plurality of crystalline carbon portions has a rod-shaped region, and the rod-shaped regions are arranged approximately parallel to one another in a direction from a first surface of the backing material toward a second surface opposite to the first surface, and The resin portion is interposed between two adjacent crystalline carbon portions. The backing material according to claim 1 or 2.

5. The backing material according to claim 1 or 2, having a thermal conductivity in accordance with JIS R1611-2010 of 35.0 W / m · K or more.

6. 3. The backing material according to claim 1, wherein the acoustic impedance is 2.0 to 6.0 Mrayl.

7. 3. The backing material according to claim 1, wherein the crystalline carbon portion has a peak ratio (G / D) in a Raman spectrum of 2.0 or more.

8. 3. The backing material according to claim 1, wherein the ultrasonic attenuation rate at a frequency of 1 MHz is 1.5 dB / mm or more.

9. 3. An ultrasonic probe comprising, in this order, an acoustic lens, an acoustic matching layer, a piezoelectric element, and the backing material according to claim 1.

Citation Information

Patent Citations

  • Ultrasonic probe backing material, method of manufacturing the same, and ultrasonic probe

    JP2019193151A

  • Ultrasonic probe, ultrasonic diagnostic device and method for producing backing material

    JP2021062170A